Role of scoring system in prediction of difficult laparoscopic cholecystectomy - Rhezhii, Delie; Goyal, Vikas; Nagpal, Nitin; Nemma, Shobhit Kumar; Gupta, Monica (International Surgery Journal, 2017)
Background: One of the most common reasons for admission to hospital is cholecystectomy and it has a mortality rate of 0.45% to 6%. Many risk factors have been found to be associated laparoscopic cholecystectomy that make it difficult like advance age, male gender, fever, obesity, previous abdominal surgeries, thick gall bladder lining, distention of bladder, presence of gall stones. There have been different scoring systems in literature that determine the risk of conversion to open cholecystectomy. The aim of present study is to determine the role of scoring system in predicting difficult laparoscopic surgery. Methods: The present prospective study was conducted for a period of 1 year in the Department of Surgery at Guru Gobind Singh Medical College, Faridkot, Punjab. The study included all the patients with symptomatic gall stones reporting to the OPD of the hospital. Patients were categorized into two groups after the surgery. Group I included patients who underwent successfully laparoscopic cholecystectomy and group II included those who were converted into an open case. In this study all the entities were provided with a score. Patients with score less than 4 were grouped as difficult. At the end of the study all the data were analyzed to see how scoring system can predict which patients will have easy or difficult laparoscopic cholecystectomy based on postoperative scoring. All the data was recorded in a tabulated form and analyzed using SPSS software. Results: The present prospective analytical study involved 112 subjects; out of these 94 were males and 18 females. The mean age of subjects was 48.2±3.7 years. There were 98 patients in Group I and 8 patients in group II who had didn’t show presence of peri cholecystic fluid. There was 1 patient in Group I and 5 patients in group II who had peri cholecystic fluid on ultrasound. There were 104 subjects with gall was thickness less than 4 mm. There were 95 patients in Group I and 9 patients in group II who had who had who had bladder wall thickness of less than 4 mm. Conclusions: The scoring tool evaluated in our study is useful in evaluating the risk of conversion of laparoscopic cholecystectomy into open cholecystectomy.